Improving your project management skills - Richman, Larry L. (Larry Leon), 1955- (American Management Association, 2012)
Based on the bestselling American Management Association seminar! If a full-fledged project management course doesnÆt fit your schedule or your budget, check out the new edition of Improving Your Project Management Skills. Based on the hugely popular American Management Association seminar of the same name, this ultra-practical reference offers powerful and repeatable project initiatives that improve processes, streamline productivity, and cut costs dramatically. YouÆll get tools, tips, charts, lists, and never-fail advice for: Planning and budgeting ò Defining project scope ò Project scheduli.